Environmental Protest and the State in France - Hayes, G. author. aut Link
XI, 246 p.
Keywords: This book discusses the issues and strategies which have characterized the environmental campaigns mounted against recent controversial infrastructure projects in France. Focusing on the changing nature of policymaking in the Fifth Republic as a key factor in the organization of each protest, Graeme Hayes asks why some protests succeed where others fail, and how we should understand the relationship between states and social movements in general.